PELAKSANAAN EXHIBITION DI SKA CO EX PEKANBARU - ", Febryanti; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Riau is one of the provinces in Indonesia which is engaged in MICE, and the city of Pekanbaru as the capital of Riau Province is a city that will move as a tourism city of MICE with various MICE activities supporting facilities. One of the venues for this mice business activity is SKA Co Ex Pekanbaru. SKA Co Ex is a convention and exhibition center and one of the properties of the Swiss Belhotel SKA Group Pekanbaru. SKA Co Ex organizes many events, including exhibition events where this exhibition will bring a lot of guests or visitors. In the implementation of exhibition there needs to be stages of implementation in order to be well organized and the event runs smoothly. The purpose of this study was to describe the implementation of exhibiton in SKA Co Ex Pekanbaru with the implementation of exibition as the basis of the concept. Data of this research was obatained from observation, interviews, and documentation, with data collection techniques using key informant purposive sampling. Based in this research, the type of exhibition held in SKA Co Ex, various stakeholders and suppliers, and the stages of implementation in which the first stage is the planning stage, where planning is first about the determination by ordering and other planning that must be prepared, and then the coordination phase is very needed in the implementation and the finally is evaluation.Keywords: Exhibition, Implemanting, SKA Co Ex